Clonal populations of Clavibacter michiganensis subsp. michiganensis are responsible for the outbreaks of bacterial canker in greenhouse tomatoes in Italy. (26th June 2015) - Ialacci, G. M.; Bella, P.; Licciardello, G.; Strano, C. P.; Eichenlaub, R.; Gartemann, K.‐H.; La Rosa, R.; Catara, V.
Abstract : Clavibacter michiganensis subsp. michiganensis (Cmm) strains, collected in greenhouses from 17 farms during tomato bacterial canker outbreaks occurring between 2005 and 2008 in Sicily, were analysed by a multiphasic approach. Population studies were conducted to investigate the possible sources of inocula. Cmm strains were characterized by PCR assays targeting virulence genes, fingerprinting techniques, metabolic profiles and virulence. These strains were comparatively analysed with Cmm strains isolated in other parts of Italy over a period of 15 years. Chromosomal genes encoding virulence determinants tomA, ppaA, chpC, and the plasmid‐encoded genes pat‐1 and celA were detected by PCR in all tested strains, except for four Sicilian Cmm strains where the pat‐1 gene was not amplified. Using BOX‐PCR, Cmm strains were differentiated into 13 haplotypes and clonal populations were identified. Cmm strains isolated from different farms in 2008 showed the same BOX‐PCR haplotype. A distinct BOX‐PCR haplotype was obtained from atypical Cmm strains lacking pat‐1 and isolated in 2006/7 from three farms. Cmm strains with two different haplotypes were detected in one farm, whereas the other farms contained strains with only a single haplotype. A new fAFLP protocol based on the amplification of Apa I/ Mse I fragments was developed and was able to differentiate C. michiganensis subspecies. Different populations were delineated for the multiple outbreaks occurring in Sicily, whereas similar populations were recorded in other Italian regions over a period of 12 years. The results are consistent with previous studies that demonstrate that Cmm outbreaks are associated with propagation material.